The Development of eLaporan a Web-Based School Reporting System - SACDAN, NADIRA SYAFIQA; DARMAN, ROZANAWATI (Applied Information Technology And Computer Science, 2026)
eLaporan is a web-based system designed to streamline reporting and provide analytical data for non-academic reporting submission in educational institution. The system addresses inefficiencies in conventional method which lead to delays issue, duplicated files, missing data, and disorganization. This system provide three different users contains Teachers, Administrator, and Principle. By developing online form and centralized database, the platform ensures seamless report generation in different device model and ensure data management. This system employs a prototyping model, enabling iterative development and refinement based on user feedback. The system primary functionalities including online form for report submission, main categories consist of Co-curricular, student affairs, school program and curriculum. Online form submission is generating PDF files for easy view report with school formatting for Administrator record. This system developed by using Laravel framework with MySQL data store. The system is anticipated to reduce manual errors by human, enhance administrative workflow, and provide cohesive repository data by offering easy-to-use system to support better decision making and communication among educators. In conclusion, eLaporan system successfully addresses key inefficiencies present in traditional reporting methods within educational institutions, particularly for non-academic event documentation.